รูปแบบและกระบวนการสร้างความเข้มแข็งของบ้าน วัด โรงเรียน ในการจัดการปัญหายาเสพติดแนวพุทธของภาคตะวันออกเฉียงเหนือ - ลีกา, จรัส (Dhammathas Academic Journal, 2017)
บทคัดย่อ การวิจัยนี้มุ่งศึกษารูปแบบและกระบวนการสร้างความเข้มแข็ง ในการจัดการปัญหายาเสพติดตามหลักพระพุทธศาสนาของบ้าน วัด โรงเรียน ในภาคตะวันออกเฉียงเหนือ ซึ่งเป็นส่วนหนึ่งของการวิจัยเรื่องรูปแบบและกระบวนการสร้างความเข้มแข็งของบ้าน วัด โรงเรียนในการจัดการปัญหายาเสพติดแนวพุทธของภาคตะวันออกเฉียงเหนือ เป็นการวิจัยเชิงคุณภาพ (Qualitative Research) โดยใช้การวิเคราะห์ข้อมูลแบบวิธีพรรณนาตามหลักอุปนัยวิธี ผลการวิจัยพบว่ารูปแบบและกระบวนการสร้างความเข้มแข็งในการจัดการปัญหายาเสพติดตามหลักพระพุทธ ศาสนาของบ้าน วัด โรงเรียน ในภาคตะวันออกเฉียงเหนือ ประกอบด้วย ๑) การสำรวจและตรวจสอบความเป็นอยู่และสภาพแวดล้อมชุมชน รวมถึงอาชีพหลักของชุมชนเพื่อเป็นข้อมูลเบื้องต้นในการสืบค้นปัญหายาเสพติดและมีการคัดแยกผู้มีพฤติกรรมเกี่ยวข้องกับยาเสพติด ๒) การประชุมผู้นำชุมชนเพื่อหาแนวทางแนวทางการป้องกันยาเสพและหามาตรการเพื่อรองรับครอบที่มีผู้ติดยาเสพติด และ ๓) การประกาศเป็นข้อตกลงของชุมชนหรือวาระของหมู่บ้าน เพื่อใช้มาตรการหรือกติกาในการรักษาชุมชนให้เข้มแข็งและห่างไกลยาเสพติด โดยมีหลักอริยสัจ ๔ เป็นกระบวนการในการแก้ปัญหายาเสพติด ซึ่งมีรูปแบบดังนี้ ๑) ทุกข์ กำหนดปัญหา (Case) ๒) สมุทัย หาสาเหตุของปัญหา (Cause) ๓) นิโรธ วิธีแก้ปัญหา (Clear) และ ๔) มรรค ลงมือแก้ปัญหา (Crack) Abstract The purpose of research titled ‘The model and process to create strength of villages-monasteries-schools on the problems addictive drug tackling according to Buddhism in the northeastern region’ is to study the form and process to create the strength on destroying the addictive drug problem following the Buddhist principles of villages, temples and schools in the northeastern Region as being qualitative research by descriptive analysis on the inductive principles. The result was found that: The forms and process of the model and process to create strength of villages monasteries-schools on the problems addictive drug tackling according to Buddhism in the northeastern region must be 1) Survey and observation on the life living and environment of community on their main occupations in order to have basic data for seeking the addictive drug problems and for classifying the persons who had behaviors concern with it. 2) The researcher had appointed the people in village for joining the way to protect that problem and find the defensive measure to accept the drug addicted families, And 3) An announcing as being the community’s promise in order to use this measure and treaty protecting the community with strength and farness of addictive drug by four noble truths as being the process of solving that problem as follow; 1. Dukkha to identify problem (case), 2. Samudhaya- origins of suffering (causes), and 3. Nirodha-solving problems (clear) and Magga- take action to solve problems (crack).